280. VATS (Video Assisted Thoracoscopic Surgery) with radiological guidance in hybrid operating room: Technique standardization, organizational aspects and dose optimization. (December 2018) - Roberto, E.; Gonnet, R.; Barberis, M.; Maggi, A. De; Bergesio, F.; Baralis, I.; Grosso, M.; Chauvie, S.
Abstract : Purpose: The aim of this work was to optimize the Video Assisted Thoracoscopic Surgery (VATS) procedure through a new rotational geometry avoiding also the interference of the flat panel with infusion lines, vital monitoring equipment and intubation instrumentation. Methods: The VATS technique was performed in the Hybrid Room environment that can be used at the same time as a diagnostic room and a surgical room. The C-Arm robotic angiography acquires cone beam CT with reduced angle rotation around the patient permitting the lateral decubitus access to thoracic surgeons with two different protocols: 12sDCTLargeVolume (12s) and 5sDRBODYCARE (5s). The first one allows to scan large volumes by twisting twice around the patient. The second protocol allows to shrink the field to the region of interest with a single pass. Organ dose and REID (Risk of Exposure-Induced Death) were estimated with Monte Carlo methods in PCXMC. Results: The initial and final positions of the C-Arm rotation were changed from −170, +30 to −100, +100 in the 5s protocol reducing the risk of collision in case of critical cases (external lesions), wherever the bed is located. After optimization we reduced the dose of 80% in the 12s protocol and of 8.5 times in the 5s. the organ dose and REID are shown in the table. Conclusions: VATS is a rapidly emerging surgical technique for the excision of lung nodules that permits to perform radical surgery of lung cancers to a larger cohort of patients and with a longer expectancy of life respect to conventional surgery. We optimized the protocol by changing rotational departure and arrival position avoiding collisions and reducing the dose.